Stability of a new geopolymer grout: Rheological and mechanical performances of metakaolin-fly ash binary mixtures. (30th August 2018) - Aboulayt, Abdelilah; Jaafri, Reda; Samouh, Hamza; Cherki El Idrissi, Anass; Roziere, Emmanuel; Moussa, Redouane; Loukili, Ahmed
Highlights: Alkali-activated grout mixtures were designed using metakaolin, fly ash, and xanthan gum. Rheological behaviour influenced by the viscosity of the solution and the packing density of powders. Evolution of elastic modulus combined with isothermal calorimetry to monitor setting and hardening. Strength and volume stability affected by increasing fly ash proportion. Abstract: The evolution of technical and environmental requirements fosters the development of geopolymer based grouts for soil reinforcement. Geopolymer based materials actually have several advantages but the improvement of their rheological performances remains a challenging task, as the raw materials, especially sodium silicate and metakaolin, do not have favorable properties and the main chemical admixtures used to optimize cement-based materials have not been found compatible. As mix-design takes into account the performances in both fresh and hardened states, a comprehensive study is necessary to develop geopolymer grouts based on metakaolin-fly ash-stabilizer mixtures. Fly ash allowed reducing the viscosity and increasing the setting time and the stabilizer provided the fresh mixes with better homogeneity and stability. At constant liquid to solid ratio, the packing density of the powders actually increases with fly ash proportion. Fly ash affected the mechanical properties, especially at replacement rates of 40% and higher, due to combined effects of reduced reactivity and higher packing density of the powders. This could be shown by a new methodology combining the monitoring the elastic properties with isothermal calorimetry for understanding the early-age behavior and the distinction between the geopolymerization stages. The addition of xanthan gum had a beneficial effect on the stability of grouts, by acting on the activation solution without having any significant effect on the geopolymerization reaction.